HISTORY OF PHOTOGRAPHY IN INDONESIA ([S.l.])
1 online resource
Keywords: As a former colonized nation, Indonesia has a unique place in the history of photography. A History of Photography in Indonesia: From the Colonial Era to the Digital Age looks at the development of photography from the beginning and traces its uses in Indonesia from its invention to the present day. The Dutch colonial government first brought the medium to the East Indies in the 1840s and immediately recognized its potential in serving the colonial apparatus. As the country grew and changed, so too did the medium. Photography was not only an essential tool of colonialism, but it also became part of the movement for independence, a voice for reformasi, an agent for advocating democracy, and is now available to anyone with a phone. This book gathers essays by leading artists, scholars, and curators from around the world who have worked with photography in Indonesia and have traced the evolution of the medium from its inception to the present day, addressing the impact of photography on colonialism, independence, and democratization.